A comprehensive review on structural joining techniques in the marine industry. (1st June 2022) - Delzendehrooy, F.; Akhavan-Safar, A.; Barbosa, A.Q.; Beygi, R.; Cardoso, D.; Carbas, R.J.C.; Marques, E.A.S.; da Silva, L.F.M.
Abstract: Exposure to aggressive environmental conditions and specific loads necessitate precise material selection and manufacturing techniques. Techniques such as overlamination, welding, adhesive bonding, mechanical joining, and hybrid joining are currently used to join different marine structures components. This review groups the published investigations to cover a wide range of geometries, materials, and loading types and organizes them in a chronological context. Comparing joining methods shows that each technique has a considerable potential to be employed in the various marine industry sectors corresponding to the desired application. Besides the significant strength, poor fatigue life is a concerning issue for welding. One of the most crucial challenges in mechanical fastening is drilling holes in composite materials that damages the fibres. Adhesive bonding provides superior advantages such as higher strength to weight ratio and fatigue life, whilst the susceptibility to environmental conditions must be considered. To overcome the drawbacks of each approach, the hybrid joining technique is introduced which combines two different joining methods to achieve the optimum performance. To have the most durable, and reliable structure, major criteria such as the structure application, the fabrication process, and the tolerance of adverse environment must be considered to design the marine structures.